FESTIVAL KEGAMAAN SENI DAN OLAHRAGA DI PONDOK PESANTREN AS’ADIYAH PENGKENDEKANKECAMATAN SABBANG KABUPATEN LUWU UTARA - Lestari, Riska Dwi; Sandi, Sandi; Pratama, Muh. Asmar; A, Nurnaningsih (MAJU : Indonesian Journal of Community Empowerment, 2025)
To nurture a generation that excels academically and has noble character, programs that develop students' talents while strengthening religious values, creativity, and physical fitness are essential. The Religious, Art, and Sports Festival at Pesantren As'adiyah Pengkendekan, in collaboration with KKN-T Post VIII of As'adiyah Islamic University, serves as a platform to achieve these goals. The festival involves students from various educational levels, including Madrasah Ibtidaiyah, Tsanawiyah, and Aliyah, as well as participants from schools outside the pesantren in Sabbang and South Sabbang Districts. The event includes four key stages: (1) Observation. Identifying the need for student guidance due to low confidence and undeveloped talents; (2) Socialization. Informing schools that the festival is both a competition and a learning platform fostering creativity, sportsmanship, and religious values; (3) Preparation. Developing the festival concept through collaboration with schools, pesantren mentors, and sponsors; (4) Training. Providing guidance to both organizers and participants for effective event management and competition readiness. This festival has a significant positive impact, enhancing students' academic and non-academic growth, fostering character building, creativity, solidarity, and sportsmanship beyond just competition